Community-level impacts of the third sector: does the local distribution of voluntary organizations influence the likelihood of volunteering? - Mohan, John (Environment and planning, 2019)
Scholars have attributed various beneficial outcomes to the presence and density of the voluntary, third or non-profit sector in communities. One way in which the distribution of such organizations may benefit communities is through providing opportunities for volunteering. We hypothesize that the distribution of third-sector organizations has an influence, after controlling for relevant individual and area characteristics, on the likelihood of engaging in formal volunteering (defined as unpaid help given through, and to, third-sector organizations, rather than directly to individuals). Using administrative data from the Charity Commission, we classify organizations in terms of their geographical scale of operation. We then construct indicators of the distribution of charities, and their expenditures, for local authorities in England. We obtain data on volunteering by individuals from the Citizenship Survey and link this to administrative data contained in the Charity Commission register on the distribution of charities. We find that there is a positive relationship between the numbers of charities operating locally and the likelihood of volunteering. Other measures, however, including the distribution of charities operating either regionally or nationally, have no statistically significant effects. We find no relationship between a measure of the size of charities (the median expenditures of charities within local authorities) and the likelihood of volunteering. These findings are relevant beyond the UK to debates about the understanding of variations in voluntary action, and to discussions about the impact of the third sector upon communities.